Arquitetura virtual distribuída baseada em veículo: uma abordagem para estudos de compatibilidade eletromagnética em veículos militares - Kaiser, Héber de Carvalho (2021)
Automotive industry growing is directly related to the increase of tecnologies used in vehicles, independently of his size. In these aspect, the use of electronic control elements have been essencial to achieve various objectives, like engine performance, compliance to legal requirements of atmosferic emissions, resources integration of comfort and vehicle dynamics, entertainment, cybersecurity, among others. For those systems communicate between them, it applies the use of automotive networks, which, according to application, delivers required reliability and robustness. In front of that, industry and academy searches for ways to innovate and improve the automotive networks solutions. The availability of a low cost system, with minimal features to understand the control process of car embedded modules is primordial to professional growing, as well as for industry which receives new concepts and professionals with some experience. A fastest growing area in Electronic Engineering is the study of electromagnetic compatibility, that can be evaluated in a prototype system, without exposing any cars or people to risky conditions. Such study may be applied to military area, regarding to vehicle electronic systems integrity in great exposure to noisy enviroments. In military vehicles, there is a concern about being a target for tracking and pursuit systems, like air-toground and ground-to-ground missiles, which does not restrict to purely military applications (in battlefields), but also in case of very important people transportation, like presidents and state leaderships. In these situations, it is ordinary to find some vehicles as part of the convoy with specific functions of Communications, Command and Control (C3), or acting as interference signal emitter (jammer). The power of these electromagnetic signals emitted from these vehicles would be strong enough to block cellular phone signals next to the car parade. Yet, the convoy’s cars operation do not suffer from these radiations, evincing the robustness of automotive network protocols, like CAN, LIN, FlexRay, among others. This work exposes some techniques used by embedded equipment for generating interference in military or official state cars, shows other external signals to whom cars are subjected, as well as presents how CAN was designed to have a high immunity standard to electromagnetic noise.